2008
DOI: 10.2478/v10001-008-0010-3
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure Assessment for Crystalline Silica Dust: Approach in Poland and Worldwide

Abstract: Crystalline silica is a health hazard commonly encountered in work environment. Occupational exposure to crystalline silica dust concerns workers employed in such industries as mineral, fuel-energy, metal, chemical and construction industry. It is estimated that over 2 million workers in the European Union are exposed to crystalline silica. In Poland, over 50 thousand people work under conditions of silica dust exposure exceeding the occupational exposure limit. The assessment of occupational exposure to cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Over 2 million workers in the EU are exposed to crystalline silica in mineral, fuel-energy, metal, chemical and construction industries. For example, in Poland, over 50,000 individuals are exposed at work to silica dust exposure exceeding the occupational exposure limit [38]. In 2012, diesel engine exhaust was classified as a Group 1 carcinogen mainly on the basis of robust epidemiological studies of occupational exposure among nonmetal miners and railroad and truck workers, showing an excess risk of lung cancer.…”
Section: Occupational Exposuresmentioning
confidence: 99%
“…Over 2 million workers in the EU are exposed to crystalline silica in mineral, fuel-energy, metal, chemical and construction industries. For example, in Poland, over 50,000 individuals are exposed at work to silica dust exposure exceeding the occupational exposure limit [38]. In 2012, diesel engine exhaust was classified as a Group 1 carcinogen mainly on the basis of robust epidemiological studies of occupational exposure among nonmetal miners and railroad and truck workers, showing an excess risk of lung cancer.…”
Section: Occupational Exposuresmentioning
confidence: 99%
“…Occupational exposure frequently occurs in a variety of industries, such as metal and coal mining, construction, and clay manufacturing. Recent reports have indicated that more than 1.7 million workers in the United States (1), more than 2 million in Europe (2, 3), and more than 23 million in China (4) have been occupationally exposed to crystalline silica dust. In ambient air, crystalline silica can be easily generated from industrial operations, volcanic explosions, and sandstorms.…”
mentioning
confidence: 99%
“…Their environmental crimes often involve the use of organized syndicates to illegally manage their toxic waste (Simon, 2000). Transnational corporations have likewise been found to be responsible for the production and emission of a multitude of carcinogenic pollutants resulting from the manufacture and processing of a variety of industrial commodities including plastics, chemicals, and numerous natural resource extraction processes (Baan, 2007;Blatt, 2006;Easter & Konishi, 2006;Garshick et al, 2008;Goldstein & Goldstein, 2002;Huff, Jacobson, & Davis, 2008;Maciejewska, 2008;Olfert, Felknor, Delclos, 2006;Perera et al, 2008;Richardson, 2008). An abundance of scientific evidence links industrial waste, fossil fuel extraction and processing, nuclear power plant operations, nuclear waste disposal, and the production of a variety of consumer products to a plethora of health problems including cancer and cancer mortality (Faber, 2008;Goldstein & Goldstein, 2002).…”
Section: Introductionmentioning
confidence: 95%